Contributions of Rural Women Farmers to Community Development in Ovia Northeast, Edo State, Nigeria - Osabuohien, Julius I.; Ohikhobo, M. O. (NIU Journal of Social Sciences, 2026)
This study investigated the contributions of rural women farmers to community development in Ovia North-East Local Government Area of Edo State, Nigeria. A multi-stage sampling technique was employed to select 120 respondents from four active farming communities. Primary data were collected using structured questionnaires analyzed with descriptive statistics and regression models. Findings revealed that the mean age of respondents was 50 years and were active farmers and many possessed long farming experience (mean= 13 years). Majority (79.8%) were married and have large households of 6–10 persons (58.7%). They engaged in divers farming activities like: crop production, livestock rearing, fish farming marketing and few others which strengthen local food systems, stabilize household livelihoods, and stimulate grassroots development. Rural women contribution to community development are mainly in the areas of food production (96%), paying of taxes (76.0%) among others. Income was directed mainly toward household welfare with 98% spent on household needs, 75.96% on children’s schooling, 36.54% reinvested into farms, and 11.54% used for community dues, showing how women convert limited income into long-term community and household well-being. Regression analysis further indicated that monthly income (p = 0.001) and household size (p = 0.001) significantly influenced women’s contributions, explaining 40.8% of the variation in community development participation. The study therefore concludes that empowering rural women is essential for sustainable grassroots development. The study recommends that government and NGOs expand gender-responsive financial inclusion programmes targeting rural women farmers; extension services be redesigned to target rural women more; women’s roles in community decision-making be strengthened; and access to land, inputs, and supportive infrastructure be improved to enhance productivity and enable women to contribute even more meaningfully to community development. Keywords: Rural women, contribution, community development, constraints